The Information Literacy Standards for the Information Professionals’ Education in the 21st Century - Mesut Yalvaç (Türk Kütüphaneciliği)
The main aim of this research is to investigate main information literacy standards for the information professionals' education in the 21st century. In the study, subject is examined under these titles: ‘concepts of the information and the information literacy’, ‘relationship of the information literacy and the information technology’, ‘the information literacy both in the higher education and the education of the information professionals ’, ‘the information literacy standarts in the education of the information professionals’.